Keefektifan Tingkatan Pembelajaran Inkuiri (Level of Inquiry) terhadap Peningkatan Keterampilan Proses Sains pada Pengetahuan Awal Siswa yang Berbeda - Salim; Suryaman; Retno Danu Rusmawati (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2019)
This study aims to determine the differences in the effectiveness of inquiry learning on several levels towards improving science process skills with different initial knowledge. The study design uses quasi-experimental treatment with pre-posttates in the control group and the experimental group. Class X MAN Sampang and SMAN 1 Sampang students in 2018/2019 school year. Samples were grouped into three treatment groups. The experimental group 1 applied level 3 inquiry learning (PIT-3), the experimental group 2 applied level 4 inquiry learning (PIT-4) and the control group applied level 2 inquiry learning (PIT-2). The science process skills test uses multiple choice objective questions with a test reliability of 0.77. Data analysis uses ANOVA test. This study concludes level 2 (PIT-2), level 3 (PIT-3) and level 4 (PIT-4) inquiry learning has a difference in effectiveness in improving science process skills. Improved science process skills of students with different initial knowledge, most effective in the application of inquiry level 3 (PIT-3) learning, students with high and low initial knowledge gain a higher gain than the application of level 2 (PIT-2) and level 4 inquiry learning (PIT-4).